2021
DOI: 10.3390/diagnostics11081335
|View full text |Cite
|
Sign up to set email alerts
|

Does Adding Standard Systematic Biopsy to Targeted Prostate Biopsy in PI-RADS 3 to 5 Lesions Enhance the Detection of Clinically Significant Prostate Cancer? Should All Patients with PI-RADS 3 Undergo Targeted Biopsy?

Abstract: Introduction. Our aim was to assess the value of adding standard biopsy to targeted biopsy in cases of suspicious multiparametric magnetic resonance imaging (mp-MRI) and also to evaluate when a biopsy of a PI-RADS 3 lesion could be avoided. Methods: A retrospective study of patients who underwent targeted biopsy plus standard systematic biopsy between 2016–2019 was performed. All the 1.5 T magnetic resonance images were evaluated according to PI-RADSv.2. An analysis focusing on the clinical scenario, lesion lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…When analysing predictors for the upgrading to sPC by additional SB, we found that men with PI-RADS 2-4 lesions were more likely to have their TB results upgraded by SB compared to PI-RADS 5 men. These results are in accordance with previous studies [ 7 , 18 , 19 , 20 ]. Ahdoot et al proposed the patient’s PI-RADS score as a promising tool to select the optimal biopsy strategy in terms of omitting SB in men harbouring a PI-RADS 5 lesion [ 10 ].…”
Section: Discussionsupporting
confidence: 94%
“…When analysing predictors for the upgrading to sPC by additional SB, we found that men with PI-RADS 2-4 lesions were more likely to have their TB results upgraded by SB compared to PI-RADS 5 men. These results are in accordance with previous studies [ 7 , 18 , 19 , 20 ]. Ahdoot et al proposed the patient’s PI-RADS score as a promising tool to select the optimal biopsy strategy in terms of omitting SB in men harbouring a PI-RADS 5 lesion [ 10 ].…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, nowadays the classic SB approach precluding the mpMRI pathway has lost validity. Some authors conclude that the additional value of performing SB after TB is limited in patients with PI-RADS 5 lesions with or without a PSA density (PSAD) ≥0.15 or anterior lesions and thus could be omitted ( 41 ). In contrast, others proclaim that they failed to identify those patients who might safely benefit from TB alone and recommend SB since TB/SB have a higher detection rate of csPC ( 8 , 42 ) and false negative TB missing relevant PCa in 9%–27% of heterogenous cohorts ( 7 , 10 , 11 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gomez-Gomez et al reported that standard biopsy could be safely omitted in patients with an anterior lesion and in those with a PI-RADS 5 lesion. They also reported that targeted biopsy for PI-RADS 3 lesions would be less effective in detecting csPCa and thus omitted in patients with peripheral zone lesions and a previous negative biopsy [ 26 ]. In our study, though we could not find an association between G/S upgrade and biopsy methods (targeted vs. systematic), we found that regardless of the PI-RADS score and biopsy setting (initial and repeat), the detection rate of csPCa is higher in the targeted biopsy group compared with the systematic biopsy group.…”
Section: Discussionmentioning
confidence: 99%